Graded homotopy classification of Leavitt path algebras over finite primitive graphs - Arnone, Guido (2025)
We show that the graded Grothendieck group classifies unital Leavitt path algebras of primitive graphs up to graded homotopy equivalence. To this end, we further develop classification techniques for Leavitt path algebras by means of (graded, bivariant) algebraic K-theory.